Caracterização molecular, morfofuncional e biotecnológica de espécies do gênero Carapa - Nascimento, Gleisson de Oliveira (Instituto Nacional de Pesquisas da Amazônia – INPA, 2017)
Plant species belonging to the Meliaceae botanical family, specifically those of the Carapa genus, are important sources of primary products, presenting excellent quality wood and the oils extracted from the seeds are widely used in traditional medicine and in the manufacture of cosmetics. Despite considered as different species, there are still uncertainties in defining the plant species belonging to this group, especially those with morphological similarities. The precise identification is an important step to establish different types of uses for this species, especially in their growth environment. Thus, the objective of this study was to investigate the molecular, morpho-functional and biochemical bases, as well as potential biotechnological applications for plant species of the Carapa genus, aiming to obtain information in order to confirm or not the differences between cryptic species belonging to this taxonomic group. Leaf, seed and fertile Carapa (Carapa guanensis and C. vasquezii species) material samples were collected from different Amazon regions (Acre, Rodônia and Amazonas) for analyzing genomic DNA, oils, carbohydrates and mineral nutrients. In this work, molecular characterization was performed using two chloroplastidics and nuclear primers (Psba-trnH, rbcL and ITS, respectively). In addition, the lipid profile was characterized for plant species collected in the different locations considered in this study. A study of the primary reserve mobilization was conducted to investigate the different strategies of the species during germination and initial seedling growth. The applicability of the oils in in vitro cultivation was tested for plant species of the Carapa genus to verify the feasibility of its use in the control of phytopathogenic fungi. In addition, the establishment of in vitro propagation protocols from zygotic embryos and nodal segments of the species was possible. Therefore, it was proven by molecular markers and lipid profile that the different taxonomic units have a tendency to form distinct groups, and that the groups can also be defined by the origin of the samples, probably because of the influence of the growth environment (Chapter I). The studied species of the Carapa genus present morpho-functional divergences that are mainly associated to the morphological characteristics of seeds (hilum length), leaf apex and content of primary metabolites (carbohydrates, lipids and proteins) (Chapter II). Regarding the different strategies of primary and nutrient reserve mobilization, in general, C. guianensis showed higher values for carbohydrate, lipid, soluble protein, and macro and micro nutrient contents. In contrast, there was greater stability of primary metabolite mobilization in C. vasquezii during the analyzed stages (Chapter III). The percentages of mycelial growth inhibition of phytopathogenic fungi were promising, given that the highest results were attributed to concentrations above 62.5 μL/mL of oils extracted from C. vasquezii seeds (Chapter IV). The in vitro cultivation of C. guianensis and C. vasquezii made possible the obtaining of complete seedlings using zygotic embryos and callus formation using nodal segments (Chapter V). The results suggest a few divergences regarding the molecular and morpho-functional characteristics in plant species of the Carapa genus. The use of molecular and chemical markers can aid in the identification and indication of the origin of the samples. The oils extracted from seeds of these species showed inhibition of fungal mycelial growth. The in vitro propagation of Carapas has potential for the production of selected clones, with the need to improve the protocol regarding asepsis of the explants. Keywords: Andiroba, molecular markers, primary metabolites, vegetable oils, lipid profile and forest seeds.
Keywords: Andiroba; Óleos vegetais.; Marcadores moleculares